Friendship at the margins : discovering mutuality in service and mission - Heuertz, Christopher L., 1971-; Pohl, Christine D. (Downers Grove, IL : IVP Books, 2010)
"Chris Heuertz, international director of Word Made Flesh, and theologian and ethicist Christine Pohl show how friendship is a Christian vocation that can bring reconciliation and healing to our broken world. They contend that unlikely friendships are at the center of an alternative paradigm for mission, where people are not objectified as potential converts but encountered in a relationship of mutuality and reciprocity."--From back cover
The vocation of relationship -- Reconnecting righteousness and justice through friendships -- Mutuality in mission -- Naming the ambiguities and tensions -- A spirituality fit for the margins.
Includes bibliographical references.
Keywords: Church work with the poor; Word Made Flesh (Organization); Friendship -- Religious aspects -- Christianity